Effects of marble sludge incorporation on the properties of cement composites and concrete paving blocks. (20th January 2016) - Mashaly, Ahmed O.; El-Kaliouby, Baher A.; Shalaby, Basel N.; El – Gohary, Amr M.; Rashwan, Mohammed A.
Abstract: The continuous development of the ornamental stone industry in Egypt due to the increasingly great demand of the Egyptian stones, whether on the local or the international scale, led to a continuous and increasing accumulation of huge quantities of marble wastes in different forms which may reach about 55–85 % of the total quarrying and processing stages. The main objective of this study is to demonstrate the possibility of using marble wastes (marble sludge) as a cement substitute in cement and concrete production. The current study presents the characterization of marble sludge and various practical formulations of cement composites and concrete mixtures. With regard to cement composites pastes, the marble sludge was substituted for cement binder up to 40% at certain proportions of 0%, 10%, 20%, 30% and 40%. The mineralogical, physical and mechanical properties of both the fresh and hardened cement composites pastes and hardened concrete mixtures including marble sludge were determined at 3, 7 and 28 d, curing times for cement composites and 28 d for concrete products according to standard test methods (ASTM and BS EN) and the results were compared with the specification requirements of these standards. The results showed that using up to 20% of marble sludge, improved the physical and mechanical properties of concrete products.